META ANALYSIS THE EFFET OF INTEGRATED SCIENCE STUDENTS’ WORKSHEETS TOWARDS JUNIOR HIGH SCHOOL STUDENTS’ LEARNING OUTCOMES - Nike Maila Forma; Yurnetti Yurnetti (Universe, 2021)
Science learning in the 2013 curriculum is carried out in an integrated manner. The worksheets used have not been integrated and the students' science learning outcomes low. There aremany studies related to the effect of integrated science worksheets on student learning outcomes. Notmany studies have looked at research trends overall. Based on these problems, a literature analysis was carried out regarding the effect of Integrated Science Worksheets in improving junior high school student learning outcomes. The purpose of this study was to see the effectiveness of the Integrated Science Worksheet for junior high school students' learning outcomes. Method The research is descriptive followed by meta-analysis. The study population is thearticles premisesn problem of the influence of integrated science worksheets on learning outcomes of junior high school students published in the journal ISSN with a sample of 13articles. The results of research worksheets effectively improve learning outcomes student. according to the analysis of research results in the literature and supported by the average effect size. Theinfluence of Integrated Science Worksheets in class VII is equal to (1.026), the method or approach used is the scientific approach (1.391) and student learning outcomes in the knowledge aspect (0.917).